LIODetect®TB-ST: Evaluation of novel blood test for a rapid diagnosis of active pulmonary and extra-pulmonary tuberculosis in IGRA confirmed patients - La Manna, Marco Pio; Tamburini, Bartolo; Orlando, Valentina; Badami, Giusto Davide; Di Carlo, Paola; Cascio, Antonio; Singh, Mahavir; Dieli, Francesco; Caccamo, Nadia (Tuberculosis (Edinburgh, Scotland), 2021)
Because of the current limits of immunological tests in the diagnosis of tuberculosis there is a need to identify new and rapid tests that can be carried out on a large scale in endemic countries and useful in the identification of infected subjects, but also able to discriminate those with latent infection from subjects with active. We have taken into consideration and analysed the LIODetect®TB-ST Tuberculosis Rapid Test, a membrane test for the qualitative detection of specific IgG, IgA, and IgM antibodies against Mycobacterium tuberculosis, performed on serum, plasma, or whole blood.85 samples positive to QuantiFERON TB-GOLD PLUS test were processed using this test and the results obtained were concordant with clinical diagnosis.To our knowledge, the LIODetect®TB-ST Tuberculosis Rapid Test is the only test; that identifies active tuberculosis disease with high sensitivity and specificity and its use might be of help in the diagnosis of tuberculosis, especially in endemic countries.